A natural knockout of the MYO7A gene leads to pre‐weaning mortality in pigs. (6th May 2021) - Derks, M. F. L.; Megens, H.‐J.; Giacomini, W. L.; Groenen, M. A. M.; Lopes, M. S.
Summary: The pig breeding system provides a unique framework to study recessive defects and the consequence on the phenotype. We examined a commercial synthetic Duroc population for recessive defects and identified a haplotype on chromosome 9 significantly affecting pre‐weaning mortality. To identify the causal variant underlying the mortality, we examined sequence data of four carrier animals and 21 non‐carrier animals from the same population. The results yield a strong candidate causal stop‐gained variant (NM_001099928.1:c.541C>T) affecting the MYO7A gene in complete linkage disequilibrium with the lethal haplotype. The variant leads to an impaired (p.Gln181*) MYO7A protein that truncates 2032 amino acids from the protein. We examined a litter from a carrier sow inseminated by a carrier boar. From the resulting piglets, two confirmed homozygous piglets suffered from severe balance difficulties and the inability to walk properly. The variant segregates at a carrier frequency of 8.2% in the evaluated population and will be gradually purged from the population, improving animal welfare. Finally, this 'natural knockout' will increase our understanding of the functioning of the MYO7A gene and provides a potential model for Usher syndrome in humans.